GeoGebra teaching methodology” program to improve mathematical competence in an educational institution, Cusco 2023 - Sonco Jara, Margen David (2024)
The general objective of this research was to establish the effect of the application of the GeoGebra teaching methodology program on mathematical competence in an educational institution, Cuzco 2023. In order to carry it out, a quantitative approach, basic typology and quasiexperimental design were used. For this purpose, two groups (control and experimental) were selected, each comprising 28 students. A test was carried out in 2 moments: a pretest and a posttest after a total of 10 sessions where the main mathematical competences were strengthened through the use of GeoGebra software. After applying the tests, since the data were parametric, Student's t statistical analysis was used. The results showed that the application of the program significantly improved mathematical competence, since the p-value was less than 0.05. In the case of the specific results, the application of the software did not have an impact on the improvement of the ability to solve problems of regularity, equivalence and change (p value= 0.648). On the other hand, GeoGebra did have a positive impact on the improvement of the dimension solves problems of shape, motion and location (p value= 0.000).